Study of the influence of recycling aluminum on the cyclic material behavior for chill cast AlSi7Mg0.3 (Fracture and Structural Integrity, 2026)
Automotive industry and mechanical engineering strive to drastically reduce the carbon footprint of their products. This becomes increasingly important as aluminum usage grows for lightweight, efficient components. Nevertheless, cast aluminum products suffer from a lack of alloys bearing higher fractions of recycling content, though their availability is crucial. Using recycling aluminum in gravity die casting offers high potential for CO2 reduction, but the effect of increasing accompanying elements like Cu, Zn or Fe on cyclic material behavior has not been investigated yet.Within the Fraunhofer internal research project "FutureCarProduction," the effects of secondary aluminum alloys on casting processes as well as fatigue and crash behavior of car body components are investigated. The aim is to find the optimal combination between manufacturing efficiency and durability regarding the alloy's potential to reduce carbon footprint and emissions during the product life cycle.Based on alloy AlSi7Mg0.3 used in gravity die casting for car body components, three configurations — one primary alloy and two with accompanying elements — were cast and investigated through strain and stress-controlled tests. Results showed that additions of Fe and Zn lead to slightly increased cyclic and quasi-static material strength, whereas ductility was reduced.
Keywords: Fatigue; cyclic loading; recycling; aluminum; chill casting; gravity die casting